Degree of concentration of the banking sector in B&H and the impact on the prices of banking products - Milica Bojat; Mladen Rebić (Economic Themes, 2020)
This paper tends to examine the level of concentration of the banking sector in Bosnia and Herzegovina. The main objective of the paper is to measure the level of concentration and to investigate how the concentration and type of market structure affect the prices of banking products. By monitoring the movement of key indicators, it provides an insight into the state of the B&H banking sector. By using the appropriate index (HHI, CR3), the movement of concentration levels and the shape of the market structure that prevailed in the banking market over a period of time were determined. The results show that there is a moderate concentration in the B&H banking sector, which includes monopolistic competition as a form of market structure. This means that the equilibrium level of production is achieved at a lower volume of production, at higher prices for banking products (above marginal costs), thereby reducing consumer surplus relative to a perfectly competitive market.
Keywords: D40; G21; L10; L40; 330; concentration; banking sector; HHI index; CR3 index